Implementation of Life Cycle Costing for a University Building - Peter Kaming (Indonesian Journal of Life Cycle Assessment and Sustainability, 2017)
Analysis of a design process is very important in controlling the initial costs and future costs in possession of an investment project. Therefore, it should be wise to perform a LCC analysis to determine the cost of any category contained in a building project. The analysis also provide information to see how much the total cost incurred by a development project from initial to the future cost by implementing BS ISO 15686 part 5: 2008. The purpose of this study is to identify the cost proportion and make long-term plans of a university building in term of life cycle costing in the area of Univeristy of Atma Jaya Yogyakarta (UAJY). Results of the study show that there are three groups that make up the LCC: the cost of development of the building, the operating costs, and the cost of maintenance and replacement. For a long-term plan the LCC for 25 years the percentage obtained as follows, initial development cost of Rp. 10,301,450,000 (43%), operational costs Rp. 11,085,000,000 (46%), maintenance and replacement costs Rp. 2.660.570.080 (11%).